An Analysis of Students’ Attitude in Learning English Through Blended Learning at SMA N Koto Baru - Hafiza, Hafiza; Siska, Siska; Putri, Dian Mega (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
This study aims to determine how students' attitudes seen from the behavioral, cognitive, and affective components in learning English through blended learning at SMA N 1 Koto Baru Dharmasraya. This study uses a qualitative method with data collection techniques using a total sampling technique. The participants in this study were students of class XI IPA 3 and XI IPS 4 with the total number of 57 students. The instruments of this study were questionnaire and field notes. After collecting the data, the researcher was analyze the data based on the instrumentation given. There are four steps of analyzing the data; reading / memoing, describing, classifying and interpreting Based on the results of this research, it can be concluded that students have negative attitudes in the behavioral component, and have a positive attitudes in the cognitive and affective components in learning English through blended learning.